Literacy-related factors and knowledge of patient rights charter: evidence from nurses in selected hospitals in Ghana - John Foster Atta-Doku; Gordon Abekah-Nkrumah; Jacqueline Nkrumah; Prince Owusu Adoma (BMC Nursing, 2024)
Abstract Background Systems of across the world have developed and implemented patient rights policies to protect and improve the provider-patient relationship. The Patient Charter of Ghana was developed in 2002 to improve service quality and protect patients’ rights. However, it is not yet known whether those at the frontline of healthcare delivery can read and understand the contents of the charter. While studies have explored the socioeconomic and institutional level factors related to awareness and knowledge of the Patient Rights Charter, there is a lack of literature on its readability and comprehensibility among nurses. This study assesses nurses’ knowledge of the Patient Rights Charter and associated literacy-related factors. Method An exploratory cross-sectional design and quantitative methods were used to collect data on knowledge, comprehension, and readability of the Patient Rights Charter. 205 nurses from four district hospitals in the Central Region were recruited using proportional and total enumeration sampling. Data were collected using structured questionnaires and were processed using SPSS (version 26) and an online text readability consensus calculator (version 2.0). Descriptive and inferential statistical analyses were performed, and data were presented using simple frequencies, readability statistics, and regression output. Results The results show the charter is written at a higher reading grade level; Flesch-Kincaid Grade Level (13.36), Simple Measure of Gobbledygook (11.57), and Coleman-Liau Readability Index (14.2). The average reading grade level score was 14. The Gunning Fox Index (15.40) and the Flesch Reading Ease Score (34%) show the patient charter is difficult to read and will require at least 14 years of education to be able to read. 87.3% of nurses were able to read and comprehend the charter. Very few (8.3%) read at frustration level. Nurses’ actual comprehension of the charter was the only significant predictor of knowledge of the charter. Conclusion Comprehension of the patient charter is an important predictor of its knowledge. The results emphasize the need to enhance the readability and comprehensibility of the charter for providers. Hospitals can stimulate nurses’ knowledge of the charter by simplifying the charter’s language and deliberately educating nurses on its content.